PENGARUH CERITA FABEL DIGITAL TERHADAP SIKAP KESADARAN LINGKUNGAN SISWA PADA MATA PELAJARAN IPAS DI SEKOLAH DASAR - Yasmin, Elza Alida; Sunaengsih, Cucun; Amelia Karlina, Dety (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study addresses the issue of low environmental awareness among elementary school students, which affects the integrity of the relationship between humans and nature. The objective is to utilize the influence of digital fable stories as a learning media in the IPAS subject to develop environmental awareness in children aged 7-12 years, who are in Piaget’s concrete operational cognitive development stage. The research methodology employs a quantitative approach with a quasi-experimental design. The learning approach uses the digital fable "Menjadi Surili," which contains environmental values to enhance children’s empathy and understanding of nature conservation and biodiversity as an investment for the future. The results prove that the use of the digital fable in the 5th-grade class at SDN Cimalaka III has a significant effect and impact on students’ environmental awareness attitudes. The clear differences between the experimental and control classes demonstrate the effectiveness of this media in increasing environmental awareness compared to learning methods without digital fables.